ANALISI DETERMINAN KEBERLANJUTAN BUDIDAYA IKAN HIAS GUPPY (Poecilia reticulata) DALAM MANAJEMEN REPRODUKSI AKUAKULTUR - M. Amin Haitami; Kasful Anwar; Muslim (Smart Education, 2026)
Abstract: The sustainability of guppy fish (Poecilia reticulata) aquaculture is an important aspect in supporting environmentally friendly and economically viable aquaculture development. This study aimed to analyze the determinants of sustainability in guppy fish farming based on social, economic, ecological, production technology, and reproductive management dimensions using the Multi Dimensional Scaling (MDS) approach with the RAPFISH method. Data were collected through field observations, interviews, and questionnaires, and subsequently analyzed to obtain sustainability indices, leverage values, and model reliability through Monte Carlo analysis. The results showed that all assessed dimensions were classified as moderately sustainable. The sustainability index values were 68.84 for the social dimension, 61.50 for the economic dimension, 62.60 for the ecological dimension, 59.01 for production technology, and 61.55 for reproductive management. Monte Carlo analysis indicated stable results, with small differences between rapscore and simulation values ranging from 0.06 to 1.74. The coefficient of determination (R²) ranged from 0.93 to 0.96, and stress values were low (0.13–0.16), indicating that the MDS model was reliable and had good accuracy. Among all dimensions, production technology showed the lowest sustainability index, suggesting the need for improvement in technology application, production efficiency, and environmental management. Overall, the results indicate that the sustainability of guppy aquaculture can be enhanced through integrated management focusing on technological improvement, environmental control, and optimized reproductive management supported by social and economic considerations. Keywords: sustainability, guppy aquaculture, MDS, RAPFISH, reproductive management, aquaculture. Abstrak: Keberlanjutan budidaya ikan hias guppy (Poecilia reticulata) merupakan aspek penting dalam mendukung pengembangan akuakultur yang ramah lingkungan dan berdaya saing. Penelitian ini bertujuan untuk menganalisis factor determinan keberlanjutan budidaya ikan guppy berdasarkan dimensi sosial, ekonomi, ekologi, teknologi produksi, dan manajemen reproduksi menggunakan metode RAPFISH. Data diperoleh melalui observasi lapangan, wawancara, dan kuesioner, kemudian dianalisis untuk menghasilkan indeks keberlanjutan, nilai leverage, serta uji keandalan model melalui analisis Monte Carlo. Hasil analisis menunjukkan bahwa seluruh dimensi berada pada kategori cukup berkelanjutan, dengan nilai indeks keberlanjutan masing-masing sebesar 68,84 pada dimensi sosial, 61,50 pada dimensi ekonomi, 62,60 pada dimensi ekologi, 59,01 pada dimensi teknologi produksi, dan 61,55 pada dimensi manajemen reproduksi. Hasil analisis Monte Carlo menunjukkan nilai yang relatif mendekati rapscore, dengan selisih berkisar antara 0,06–1,74, yang menandakan kestabilan hasil analisis. Nilai koefisien determinasi (R²) yang tinggi, yaitu antara 0,93–0,96, serta nilai stress yang rendah (0,13–0,16), menunjukkan bahwa model MDS yang digunakan memiliki tingkat keandalan dan ketepatan yang baik. Dimensi teknologi produksi memiliki nilai indeks terendah, mengindikasikan perlunya peningkatan dalam penerapan teknologi budidaya, efisiensi produksi, serta pengelolaan kualitas lingkungan. Secara keseluruhan, hasil penelitian menunjukkan bahwa keberlanjutan budidaya ikan guppy dapat ditingkatkan melalui penguatan teknologi. produksi, pengelolaan lingkungan yang lebih baik, serta optimalisasi manajemen reproduksi yang terintegrasi dengan aspek sosial dan ekonomi. Kata kunci: keberlanjutan, budidaya ikan guppy, MDS, RAPFISH, manajemen reproduksi, akuakultur.